The incidence of tuberculous pleurisy in mainland China from 2005 to 2018 - Chen, Shuhan; Wang, Yi; Zhan, Yuan; Liu, Changyu; Wang, Qi; Feng, Jie; Li, Yufeng; Chen, Huilong; Zeng, Zhilin (Frontiers in Public Health, 2023)
Background: Tuberculous pleurisy (TP) remains a serious problem affecting global public health at present including China. Our purpose was to comprehensively understand and identify the incidence of TP in mainland China during the past 14 years. Methods: The data of registered TP cases was acquired from the national Tuberculosis Information Management System from 2005 to 2018. We analyzed the demographics, epidemiological schema, and time-space distribution of TP patients. Finally, the potential influential factors of TP incidence were assessed, covering medical expenses per capita, GDP per capita and population density. Results: The incidence of TP was in the climb in mainland China from 2005 to 2018 and the mean incidence was 2.5 per 100,000 population. Interestingly, spring was the peak season for TP with more notification cases. Tibet, Beijing, Xinjiang and Inner Mongolia had the highest mean annual incidence. Finally, there presented a certain association between TP incidence and medical expenses or GDP per capita. Conclusions: The notified incidence of TP had an elevated trend during 2005 to 2018 in mainland China. The findings of this study provide an insight into the knowledge of TP epidemiology in mainland China, which is helpful to optimize resource allocation to reduce TP burden.